2012
DOI: 10.1515/hsz-2012-0106
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the Mycobacterium tuberculosis zinc metallopeptidase Zmp1 and identification of potential substrates

Abstract: Zinc metallopeptidases of bacterial pathogens are widely distributed virulence factors and represent promising pharmacological targets. In this work, we have characterized Zmp1, a zinc metallopeptidase identifi ed as a virulence factor of Mycobacterium tuberculosis and belonging to the neprilysin (NEP; M13) family, whose X-ray structure has been recently solved. Interestingly, this enzyme shows an optimum activity toward a fl uorogenic substrate at moderately acidic pH values (i.e., 6.3), which corresponds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Cleavage sites found in the ET-1 peptide (Fig. 3) were in accordance with the previously identified cleavage pattern for Zmp1 on other substrates (29), showing a preference for phenylalanine and isoleucine amino acid residues at the P1= position. In addition, the C-terminal as well as the N-terminal intramolecular loop structure is especially important for endothelin activity; thus, an enzymatic system might exist as a physiological mechanism for converting ET-1 to biologically inactive forms (36,37).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cleavage sites found in the ET-1 peptide (Fig. 3) were in accordance with the previously identified cleavage pattern for Zmp1 on other substrates (29), showing a preference for phenylalanine and isoleucine amino acid residues at the P1= position. In addition, the C-terminal as well as the N-terminal intramolecular loop structure is especially important for endothelin activity; thus, an enzymatic system might exist as a physiological mechanism for converting ET-1 to biologically inactive forms (36,37).…”
Section: Discussionsupporting
confidence: 89%
“…Zmp1 was previously described in M. tuberculosis (9,29) and in other bacteria, including Streptococcus parasanguis (30,31) and Porphyromonas gingivalis (32), as a protease with activity on small biologically active peptides, but no activation on endothelins was seen. In P. gingivalis, the protease showed activity against Big Endothelin (33), but the results were controversial, and ET-1 generation could not be confirmed by enzyme-linked immunosorbent assay (ELISA).…”
Section: Discussionmentioning
confidence: 98%
“…Others have shown that upregulation of Neprilysin (NEP) also reduces Aβ accumulation in the brain [81]. NEP, a zinc-dependent metalloprotease similar to IDE, cleaves and inactivates several peptide hormones including neurotensin, bradykinin, and neuropeptide FF [82]. IDE and NEP, both zinc enzymes, have comparable effects for clearing Aβ with similar catalytic action [83].…”
Section: Clinical Impact Of Insulin Degrading Enzyme (Ide) On Alzheimmentioning
confidence: 99%
“…The pH dependence of pre-steady-state and steady-state parameters was analyzed in the framework of the minimum reaction mechanism depicted in Figure 3 [21], [22], where two protonating residues are involved, according to Eqns. 7-12:…”
Section: Methodsmentioning
confidence: 99%